Hubungan Konsumsi Zat Gizi (Protein, Besi, Asam Folat, Vitamin C) dan Konsumsi Tablet Tambah Darah Dengan Kadar Hb Pada Remaja Putri Kelas 10 di SMK Negeri Tabanan - Putri, Ni Made Mia Dwi Nanda; Mataram, I Komang Agusjaya; Suarjana, I Made (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2024)
Hemoglobin is a protein molecule in red blood cells that functions as a transport medium for oxygen from the lungs to all body tissues and carries carbon dioxide from body tissues to the lungs. Hemoglobin is the part of the red blood cells that determines the presence of anemia. The purpose of this study was to determine the relationship between consumption of nutrients (Protein, Iron, Folic Acid, Vitamin C) and consumption of Blood Supplementary Tablets (TTD) with Hemoglobin (Hb) levels in female adolescents at vocational high school 1 tabanan. This type of research is an observational study with a cross-sectional design. This research was conducted in December 2022. The determination of the sample size was determined by using a simple random sampling technique. Based on the calculation results, a sample size of 78 was obtained from 355 grade 10 teenage girls at vocational high school 1 Tabanan. Data is presented with frequency tables and cross tables and then analyzed using the Spearman correlation test. The results showed that out of 78 samples, there were 55 samples (70.5%) with normal hemoglobin levels ≥12 g/dL, 64.1% sample protein consumption level was in the adequate category, 70.5% sample iron consumption level was in the adequate category, 67.9% sample folic acid consumption level in the adequate category, 64.1% of the sample consumption level of vitamin C was in the adequate category, and the consumption rate of iron supplement tablets was not consumed by all samples. The results of the statistical test showed the overall p value (p0.05), which means that there was a significant relationship between the level of consumption of protein, iron, folic acid and vitamin C and hemoglobin levels.